Evaluation of Cytotoxic and Antimicrobial Effects of Two Bt Cry Proteins on a GMO Safety Perspective. (23rd July 2014) - Farias, Davi Felipe; Viana, Martônio Ponte; de Oliveira, Gustavo Ramos; Beneventi, Magda Aparecida; Soares, Bruno Marques; Pessoa, Claudia; Pessoa, Igor Parra; Silva, Luciano Paulino; Vasconcelos, Ilka Maria; Grossi de Sá, Maria Fátima; Carvalho, Ana Fontenele Urano
Abstract : Studies have contested the innocuousness of Bacillus thuringiensis (Bt) Cry proteins to mammalian cells as well as to mammals microbiota. Thus, this study aimed to evaluate the cytotoxic and antimicrobial effects of two Cry proteins, Cry8Ka5 (a novel mutant protein) and Cry1Ac (a widely distributed protein in GM crops). Evaluation of cyto- and genotoxicity in human lymphocytes was performed as well as hemolytic activity coupled with cellular membrane topography analysis in mammal erythrocytes. Effects of Cry8Ka5 and Cry1Ac upon Artemia sp. nauplii and upon bacteria and yeast growth were assessed. The toxins caused no significant effects on the viability (I C 50 > 1, 000   µ g/mL) or to the cellular DNA integrity of lymphocytes (no effects at 1, 000  µ g/mL). The Cry8Ka5 and Cry1Ac proteins did not cause severe damage to erythrocytes, neither with hemolysis (I C 50 > 1, 000   µ g/mL) nor with alterations in the membrane. Likewise, the Cry8Ka5 and Cry1Ac proteins presented high LC50 (755.11 and >1, 000  µ g/mL, resp.) on the brine shrimp lethality assay and showed no growth inhibition of the microorganisms tested (MIC > 1, 000   µ g/mL). This study contributed with valuable information on the effects of Cry8Ka5 and Cry1Ac proteins on nontarget organisms, which reinforce their potential for safe biotechnological applications.